2018
DOI: 10.1002/ca.23216
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and location of bone spurs in anterior ankle impingement: A cadaveric investigation

Abstract: Anterior ankle impingement (AAI) results from repetitive microtrauma leading to pain and decreased dorsiflexion due to spur formation and synovial hypertrophy. Information about the prevalence of anterior spur formation in a large population, and the individual contributions of the talus and tibia to osseous impingement, is limited. A total of 670 ankle specimens from 344 individuals (n = 111 females, n = 233 males) aged 20 to 40 years at the time of death were examined. Matching tibia and talus were opposed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…12,20 A study of 670 ankle specimens from 344 cadavers found osteophytes in 21% of specimens, and spurs were significantly more prevalent in male than female and in older versus younger cadavers. 19 Sex-based differences in the incidence of osteophytes require further research. Similar to OCLs, osteophytes were significantly increased in patients with CLAI with a postinjury duration of more than 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…12,20 A study of 670 ankle specimens from 344 cadavers found osteophytes in 21% of specimens, and spurs were significantly more prevalent in male than female and in older versus younger cadavers. 19 Sex-based differences in the incidence of osteophytes require further research. Similar to OCLs, osteophytes were significantly increased in patients with CLAI with a postinjury duration of more than 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…11 In addition, these osteophytes can cause swelling and restriction to the biomechanical motion of the ankle joint. A cadaveric investigation by Talbot et al 10 revealed that spurs were found in the anterolateral talus in 78% of their specimens and also in 80% of the anterolateral portion of the distal tibial margin.…”
Section: Introductionmentioning
confidence: 96%
“…6,7 The mechanisms that create obstruction and give rise to pain in both anterior and posterior bony ankle impingements are driven by abnormalities in the morphology of ankle bones, mainly osteophytes (bone spurs) in the tibia and talus. 6,8,9 In the anterior bony ankle impingement, the pain occurs during dorsiflexion of the foot, when osteophytes on the talar neck or distal tibia entrap the soft tissues in the anterior part of the ankle joint or when these osteophytes undergo irritation because they collide with each other or receive an external force. 2,10 In posterior bony ankle impingement, on the other hand, obstruction and pain happen when during plantarflexion of the foot some soft tissues get squeezed in the area between the tibial rim or calcaneus and the bony excess of the posterior side of talus, including os trigonum and Steida's process, or when an action like a plantarflexion or an external force affects the posterior process of the talus.…”
Section: Introductionmentioning
confidence: 99%
“…Based on pathoanatomic features developing ankle impingement, it is divided into bony ankle impingement (also known as ankle impingement exostosis 4,5 ) and soft tissue ankle impingement 6,7 . The mechanisms that create obstruction and give rise to pain in both anterior and posterior bony ankle impingements are driven by abnormalities in the morphology of ankle bones, mainly osteophytes (bone spurs) in the tibia and talus 6,8,9 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation